2021
DOI: 10.1002/jcp.30369
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 channels regulate the automaticity of embryonic stem cell‐derived cardiomyocytes through stimulating the Na+/Ca2+ exchanger current

Abstract: Calcium controls the excitation–contraction coupling in cardiomyocytes. Embryonic stem cell‐derived cardiomyocytes (ESC‐CMs) are an important cardiomyocyte source for regenerative medicine and drug screening. Transient receptor potential vanilloid 1 (TRPV1) channels are nonselective cation channels that permeate sodium and calcium. This study aimed to investigate whether TRPV1 channels regulate the electrophysiological characteristics of ESC‐CMs. If yes, what is the mechanism behind? By immunostaining and subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Antagonism of TRPV1 resulted in reduced expression of cardiomyocyte marker genes ( Qi et al, 2015 ). In a similar model, Zhao et al confirmed the role of TRPV1 in Ca 2+ handling and a potential interaction with the Na + /Ca 2+ exchanger ( Zhao et al, 2021 ). These studies propose that TRPV1 may play a significant role in the Ca 2+ handling in cardiogenesis and in early stage function.…”
Section: Transient Receptor Potential Vanilloidmentioning
confidence: 84%
“…Antagonism of TRPV1 resulted in reduced expression of cardiomyocyte marker genes ( Qi et al, 2015 ). In a similar model, Zhao et al confirmed the role of TRPV1 in Ca 2+ handling and a potential interaction with the Na + /Ca 2+ exchanger ( Zhao et al, 2021 ). These studies propose that TRPV1 may play a significant role in the Ca 2+ handling in cardiogenesis and in early stage function.…”
Section: Transient Receptor Potential Vanilloidmentioning
confidence: 84%
“…Although TRPV channels in GI sensory neurons have been studied extensively ( De Petrocellis et al, 2012 ; Maurino et al, 2020 ; Grover et al, 2021 ), our study is the first to demonstrate the involvement of Ca 2+ entry via TRPV channels in the regulation of ileal Gln transport in IEC. Na + /Ca 2+ influx mediated by TRPV channels could activate bidirectional ion exchange (NCX), whose transport direction depends on Na + and Ca 2+ gradients and membrane potentials ( Zhang J. et al, 2019 ; Zhao et al, 2021 ). Furthermore, we found that NKA on the serosal side of the intestine are also involved in ileal Gln- I sc , although it is well known that NKA activity is essential to provide potential energy for epithelial ion transports.…”
Section: Discussionmentioning
confidence: 99%
“…In rodent heart models, angiotensin II induced high left ventricle end-diastolic pressure and end-diastolic pressure-volume relationships [128] . This myocardium passive force-length characteristic brings out contraction zones, and bands are prominent with the dehiscence of myofilaments in adjacent sarcomeres of the diastolic ventricular muscle [129] .…”
Section: Figure 22mentioning
confidence: 98%